CHIMERIC ANTIGEN RECEPTOR T CELLS FOR THE TREATMENT OF MULTIPLE MYELOMA - Ugo Testa; Elvira Pelosi; Germana Castelli (Mediterranean Journal of Hematology and Infectious Diseases)
Multiple myeloma (MM), characterized by abnormal proliferation of clonal plasma cells, is an incurable hematological malignancy. Various immunotherapy strategies have emerged as an efficacious approach for the treatment of MM, including monoclonal antibodies, antibody-drug conjugates, bispecific antibodies, and chimeric antigen receptor T (CAR-T) cells. Anti-B-cell maturation antigen (BCMA) CAR-T cells have revolutionized the treatment of MM patients with relapsed/refractory disease and their clinical use was approved for the treatment of these patients.